The Efficacy and Limits of Pilgrimage as Therapy for Depression - Hilario, Rozheanne Cruz (Religions, 2023)
Western notions of pilgrimage produce images of religious adherence to known beliefs and their ritual expressions. Definitions of pilgrimage have expanded in recent decades to embrace treks to sites unattached to the sacred landscapes of traditional faith groups. Along with this expansion of meanings and practices has come a wider acceptance of travel for psychological transformation. Tourism can be argued as a modulated form of pilgrimage and traditional journeys of faith overlapping with instances of entirely secular tourism. Another purpose of pilgrimage can be as a therapeutic practice for those suffering from depressive disorders and related conditions. Its efficacy as therapy, along with its limits, are discussed in clinical and personal contexts with a view to including religious as well as secular perspectives. The pragmatics of such therapy are mapped against current trends in treatment.